Th17/Treg balance and factors related to autoimmune hepatitis. Issue 4 (31st October 2022) - Xue, Miao; Feng, Junshuai; Yang, Aimin; Gao, Liping; Peng, Xuebin; Jiang, Ni; Mao, Xiaorong
Abstract: Background: Although Th17 cells and regulatory T cells play critical roles in autoimmune hepatitis, the balance between them in acute and chronic immune hepatitis is not well‐studied. The objective of this study was to explore the role of Th17/Treg balance in autoimmune hepatitis. Methods: Thirty female Wistar rats were randomly divided into the following three groups: acute model (AC), chronic model (CC), and healthy control (HC). Aspartate aminotransferase, alanine aminotransferase, and bilirubin levels were measured. Peripheral blood interleukin (IL)‐17, IL‐6, IL‐10, and transforming growth factor‐β cytokine levels were also assessed. Flow cytometry was used to detect changes in the Th17 cell and Treg cell frequency, and the Th17/Treg ratio was calculated. Results: The frequency of Th17 cells and Treg cells were both increased ( p  < 0.05) and the Th17/Treg ratio was higher in the AC group compared with those in the HC group ( p  < 0.05). Th17 cell levels were significantly lower and Treg cell levels were significantly higher in the CC group, compared with those in the AC group ( p  < 0.05). In addition, the Th17/Treg ratio was lower in the CC group compared with that in the HC group ( p  < 0.05). Conclusion: The Th17/Treg ratio was increased in the acute immune liver injury model and decreased in the chronic liver injury model. Th17/Treg imbalance may play a critical role in liver injury occurrence and development. Abstract : Th17/Treg balance and factors related to autoimmune hepatitis. Key points: Different liver damage caused by different modeling types will further explain the role of Th17/Treg imbalance in autoimmune hepatitis, and this imbalance has important implications for changes in immune status and disease progression. In this study, α‐galactosylceramide was used to establish the autoimmune hepatitis model, which shows similar pathological manifestations as that in human autoimmune hepatitis.